The Venice Ghetto : a memory space that travels - Camarda, Chiara; Sharick, Amanda K.; Trostel, Katharine G. (University of Massachusetts Press, 2022)
"The Venice Ghetto was founded in 1516 by the Venetian government as a segregated area of the city in which Jews were compelled to live. The world's first ghetto and the origin of the English word, the term simultaneously works to mark specific places and their histories, and as a global symbol that evokes themes of identity, exile, marginalization, and segregation. To capture these multiple meanings, the editors of this volume conceptualize the ghetto as a "memory space that travels" through both time and space. This interdisciplinary collection engages with questions about the history, conditions, and lived experience of the Venice Ghetto, including its legacy as a compulsory, segregated, and enclosed space. Contributors also consider the ghetto's influence on the figure of the Renaissance moneylender, the material culture of the ghetto archive, the urban form of North Africa's mellah and hara, and the ghetto's impact on the writings of Primo Levi and Marjorie Agosín. In addition to the volume editors, The Venice Ghetto features a foreword from James E. Young and contributions from Shaul Bassi, Murray Baumgarten, Margaux Fitoussi, Dario Miccoli, Andrea Yaakov Lattes, Federica Ruspio, Michael Shapiro, Clive Sinclair, and Emanuela Trevisan Semi"--